Mutualistic networks - Bascompte, Jordi; Jordano, Pedro (Monographs in Population Biology, 2013)
Mutualistic interactions among plants and animals have played a paramount role in shaping biodiversity. Yet the majority of studies on mutualistic interactions have involved only a few species, as opposed to broader mutual connections between communities of organisms. Mutualistic Networks is the first book to comprehensively explore this burgeoning field. Integrating different approaches, from the statistical description of network structures to the development of new analytical frameworks, Jordi Bascompte and Pedro Jordano describe the architecture of these mutualistic networks and show their importance for the robustness of biodiversity and the coevolutionary process. Making a case for why we should care about mutualisms and their complex networks, this book offers a new perspective on the study and synthesis of this growing area for ecologists and evolutionary biologists. It will serve as the standard reference for all future work on mutualistic interactions in biological communities.